Electrochemistry in room temperature ionic liquids: A review and some possible applications - Silvester, D; Compton, R (2006)
A review of electrochemistry in ionic liquids is presented, highlighting some particular examples, with the aim to compare any similarities and differences observed in RTILs to that observed in conventional solvents. The presence of impurities such as halide and water on the electrochemical window and viscosity of RTILs is discussed. Some fundamental electrochemical studies relating to mass transport, heterogeneous electron transfer kinetics and double-layer capacitance are compared to similar studies in conventional solvents, and the suitability of RTILs as solvents in electrochemical experiments is considered. The application of RTILs as replacements for conventional solvents in gas sensors is reviewed, focussing on the electrochemistry observed in RTILs for the following gases: oxygen, a mixture of oxygen and carbon dioxide, and ammonia. The low volatility and high thermal stability of RTILs renders them advantageous for the development of robust sensors under extreme conditions. Finally, the possibility for use of RTILs as solvents in electrosynthesis is discussed, focussing on two examples: the reactivity of electrogenerated bromine with cyclohexene, and the reduction of 4-nitrophenol. It is obvious that RTILs have the ability to offer many advantages over traditional solvents in the field of electrochemistry.